Cutaneous sarcoid‐like drug reaction caused by an anaplastic lymphoma kinase inhibitor. (15th November 2020) - Gleue, Casey A.; Shah, Kabeer; Wentworth, Ashley; Bridges, Alina
Abstract: Anaplastic lymphoma kinase ( ALK ) rearranged lung cancers represent 4% to 6% of all pulmonary adenocarcinomas, and echinoderm microtubule associated protein like 4 ( EML4 )‐ ALK fusions are the most common subgroup. Herein, we report a case of two successive drug reactions due to ALK inhibitors. A 69‐year‐old female with stage IVB EML4‐ALK fused lung adenocarcinoma developed a generalized morbilliform eruption 10 days after starting alectinib. Skin biopsy findings were consistent with a drug reaction. Her findings resolved after alectinib was discontinued. Another ALK inhibitor, lorlatinib was started and she developed multiple asymptomatic cutaneous and oral nodules 4 months later. Biopsies from these nodules showed sarcoidal granulomas without evidence of metastases or infection. ALK inhibitors are associated with numerous adverse events, including various cutaneous eruptions. However, a sarcoidal drug reaction involving the skin has not been reported. Identification of drug reactions to targeted therapy can avoid long‐term sequelae and misinterpretation of the clinical findings as disease progression or infection.